Analisis Pendapatan Usahatani Tanaman Stevia (Stevia Rebaudiana Bertoni) Di Desa Kolongan Atas Ii, Kecamatan Sonder, Kabupaten Minahasa - Isabella Meilin Keintjem; Noortje Marsellanie Benu; Elsje Pauline Manginsela (AGRI-SOSIOEKONOMI, 2022)
This study aims to analyze the income of farmers from stevia farming in Kolongan Atas II Village, Sonder District, Minahasa Regency. The research was conducted in Kolongan Atas II Village, Sonder District, Minahasa Regency. The method of data collection is the method of observation, interviews and documentation. The results showed that the income level of stevia (Stevia rebaudiana bertoni) farming in Kolongan Atas II Village, Sonder District, Minahasa Regency was Rp. 6,032,411, with revenues of Rp. 16,665,000 and a total cost of Rp. 10,632,589. Stevia farming in Kolongan Atas II Village, Sonder District, Minahasa Regency is reviewed based on the R/C Ratio feasible to cultivate because the R/C Ratio > 1, where the R/C Ratio of stevia farming is 1.56. Stevia farming in Kolongan Atas II Village, Sonder District, Minahasa Regency in terms of Break Even Point analysis based on a production unit of 138,276/kg dry stevia leaves, which means the production of 138,276/kg dry stevia leaves can cover the total costs incurred while based on the value of BEP production price shows Rp. 2,091 which means that the selling price of stevia leaves of Rp. 2,091 has reached the point of return of principal. From the BEP calculation, it shows where the BEP of production prices and BEP of production units have reached the break-even point, which means that stevia farming is neither profitable nor losing.